KEPEDULIAN PERS TERHADAP PENDIDIKAN (Studi Analisis Isi Berita Pendidikan Anak di Nanggroe Aceh Darussalam Pasca-Bencana Tsunami Pada Harian Kompas dan Harian Media Indonesia) - Amalia, Ayu (Jurnal The Messenger, 2010)
This research is conducted to describe caring extent of Kompas and Media Indonesia towards child education in Nanggroe Aceh Darussalam province after tsunami disaster, using content analysis approach. Data was analyzed using intercoder reliability to measure degree of reliability between coders and media. Agenda Setting and Social Responsibility theories are used to depict media roles on instructing what should be considered by daily readers, in order to portray media social responsibilities, indicating media regard ness. Research final gains, showing that Kompas and Media Indonesia, as printed mass media representations, possessing poor average of caring extent towards child education in post-apocalyptic region, by the amount of 42, 86 %. Amongst seven indicators of research, there are only three indicators that refer to significant degree of caring extent foreshortening medias social responsibility, i.e; news title readability applying substantive method, using comprehendable words; informant selection congruent with news theme; news angle emphasizing certain indicator taken from 5W+1H concept.